2008
DOI: 10.1186/1471-2407-8-78
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulator PSK induces in vitro cytotoxic activity in tumour cell lines via arrest of cell cycle and induction of apoptosis

Abstract: Background: Protein-bound polysaccharide (PSK) is derived from the CM-101 strain of the fungus Coriolus versicolor and has shown anticancer activity in vitro and in in vivo experimental models and human cancers. Several randomized clinical trials have demonstrated that PSK has great potential in adjuvant cancer therapy, with positive results in the adjuvant treatment of gastric, esophageal, colorectal, breast and lung cancers. These studies have suggested the efficacy of PSK as an immunomodulator of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 22 publications
0
35
1
Order By: Relevance
“…A presence of LPS/other mitogens in these plant extracts argues in favor of this explanation. Such mitogens have been reported by other investigators to possess a wide range of anti-tumor, immunomodulatory, and antioxidation properties (Benjamini et al, 2000;Ben Ammar et al, 2007;Jiménez-Medina et al, 2008). Nevertheless, the data with the extracts alone (see Figure 3A) still seem incongruous with the other findings reported here; apart from a potential "mitogen presence" in the plant extracts themselves, it remains uncertain as to how this "stimulation" is occurring.…”
Section: Discussioncontrasting
confidence: 56%
“…A presence of LPS/other mitogens in these plant extracts argues in favor of this explanation. Such mitogens have been reported by other investigators to possess a wide range of anti-tumor, immunomodulatory, and antioxidation properties (Benjamini et al, 2000;Ben Ammar et al, 2007;Jiménez-Medina et al, 2008). Nevertheless, the data with the extracts alone (see Figure 3A) still seem incongruous with the other findings reported here; apart from a potential "mitogen presence" in the plant extracts themselves, it remains uncertain as to how this "stimulation" is occurring.…”
Section: Discussioncontrasting
confidence: 56%
“…Cell cycle analysis revealed that MC induces significant cell cycle arrest at G2/M phase from 3.1% (control) to 12.2% (0.5 mg/ml MC) ( Table I). As previously demonstrated cell cycle arrest at G2/M was induced by A. blazei in gastric epithethelial cells (68) or by cordyceptin isolated from C. sinensis in bladder cancer cells (69), whereas protein-bound polysaccharide (PSK) isolated from the C. versicolor induced cell cycle arrest at G0/G1 in a variety of cancer cells (28). Interestingly, different extract from G. lucidum demonstrate specific effects on cell cycle progression.…”
Section: Induces Cell Cycle Arrest At G2/m Phasementioning
confidence: 75%
“…Therefore, C. versicolor induced apoptosis of breast cancer cells through p53 and Bcl-2 dependent and independent mechanisms (26) suppressed cell proliferation, and induced apoptosis of leukemia cells by mechanisms including inhibition of transcription factor NF-κB and down-regulation of expression of COX-2 (27). Moreover, direct cytotoxic effect of PSK, through the cell cycle arrest at G0/G1 phase and induction of apoptosis associated with the caspase-3 expression, was reported in various tumor cell lines derived from leukemia, melanomas, fibrosarcomas and cervix, lung, pancreas and gastric cancers (28).…”
Section: Introductionmentioning
confidence: 99%
“…PSK-induced antiproliferative activity against HL-60 cells is caused, at least in part, by the induction of apoptosis, which has been reported, but has yet to be fully characterized (9)(10)(11). Comprehensive analysis of apoptosis-related protein expression upon PSK treatment of HL-60 cells showed altered expression of several proteins.…”
Section: Discussionmentioning
confidence: 99%